Synthesis and Phase Transition of Poly(N-isopropylacrylamide)-Based Thermo-Sensitive Cyclic Brush Polymer - Tu, Xiaoyan; Meng, Chao; Liu, Zhe; Sun, Lu; Zhang, Xianshuo; Zhang, Mingkui; Sun, Mingrui; Ma, Liwei; Liu, Mingzhu; Wei, Hua (Polymers, 2017)
Polymers with advanced topological architectures are promising materials for wide applications due to their structure-generated unique properties different from that of the linear analogues. The elegant integration of stimuli-responsive polymers with such advanced architectures can create novel materials with virtues from both moieties, are thus a hot subject of research for both fundamental and practical investigations. To fabricate cyclic brush polymer-based intelligent materials for biomedical applications, herein, we designed and synthesized thermo-sensitive cyclic brush polymers with poly(N-isopropylacrylamide) (PNIPAAm) brushes by controlled living radical polymerization using cyclic multimacroinitiator. The thermo-induced phase transition behaviors of the resultant cyclic brush polymers with different compositions were investigated in detail by temperature-dependent optical transmittance measurements, and compared with the properties of bottlebrush and linear counterparts. Interestingly, the cloud point transition temperature (Tcp) of cyclic brush PNIPAAm could be regulated by the chain length of PNIPAAm brush. Although the bottlebrush polymers with the same composition exhibited similarly structurally dependent Tcps behaviors to the cyclic brush polymers, the cyclic brush PNIPAAm did show higher critical aggregation concentration (CAC) and enhanced stability against dilution than the bottlebrush counterpart. The readily tailorable Tcps together with the ability to form highly stable nanoparticles makes thermo-sensitive cyclic brush PNIPAAm a promising candidate for controlled drug delivery.